Suistanable Tourism Development in The Economic - arista khairunnisa (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
This study aims to determine the sustainable tourism development model in Pujon Kidul Village and to determine the impact of sustainable tourism development on community economic development in Pujon Kidul Village. The research method is qualitative research. Datasource of primary data obtained through interviews on headman in Pujon Kidul village, and tourism operators and secondary data from village records and previous research . Collecting data through interviews, observations and documentation. The results of the research found that the sustainable tourism development model in Pujon Kidul Village uses the Community Based Tourism model which involves the community which means that the community is the owner, manager and actor of tourism activities. The impact of sustainable tourism development on economic development is to first reduce poverty, which was originally the number of poor people of 375 people in 2016 reduced to 275 people in 2018 . Second eliminate disparities in the availability of jobs for rural communities. Third, the availability of funds for the development of other fields in the form of increasing village income from year to year. Fourth, public order is maintained in the form of decreased social dysfunction behaviors in society. By way of tourism in the village Pujon Kidul role is important in the development of economic society .